Dynamics of trophic structure for the epipelagic community in the western Bering Sea - Alexander V. Zavolokin; Vladimir I. Radchenko; Vladimir V. Kulik (Известия ТИНРО)
Changes of quantitative composition and trophic structure of the nekton community in the western Bering Sea are considered for the last decades and role of pacific salmons in dynamics of trophic flows is evaluated in dependence on their abundance using the ecosystem model Ecopath. Two models are developed that describe trophic structure of the community in two cases: 1) low biomass of salmons and high biomass of walleye pollock (in 1980s, the year 1986 is analyzed as an example) and 2) decreased pollock biomass and increasing salmon biomass (in 2000s, the year 2006 as an example). Besides, a hypothetical situation is modeled with the salmon biomass multiplied by 1.5 relative to its level in 2006. Significant decrease of pollock abundance between 1980s and 2000s caused twofold reduction of total food consumption by nekton species; the heightened consumption by salmons and squids in the 2000s compensated only a small part of this reduction. However, the tenfold increase of salmons biomass changed their main diets with lowering of the prey trophic level from amphipods and squids to euphausiids, copepods, and pteropods. Now the salmons are the only numerous predator group of the fourth trophic level in the upper pelagic layer of offshore waters in the western Bering Sea. Due to their high trophic plasticity, they can feed by wide range of prey belonged to 2-3rd trophic levels that supplies them by a large amount of food. Even in the modeled case of increasing of the salmons biomass in 1.5 times relative to the level of 2000s, the current level of forage resources is able to support their populations. There is concluded that carrying capacity of the western Bering Sea is excessively sufficient for pacific salmons in periods of their high abundance.